野生动物与荒野地: 基督教的观点 - Rolston, Holmes, 1932-2025, author; Diqiuri Chubanshe, Taiwan, publisher (Colorado State University. Libraries, 1997)
The principal focus of Biblical faith is the culture established in the land. At the same time the Bible is full of constant reminders of the natural givens. Justice is to run down like waters, and the land flows with milk and honey. The fauna is included within the covenant. Life in artificial environments, without experiencing the divine creation is ungodly. Bringing a perspective of depth, Christian conviction wants sanctuaries not only for humans, but also for wildlife.
Wildlife and wildlands: a Christian perspective
Ye sheng dong wu yu huang ye di: Ji Du Jiao de guan dian
Text in Chinese.
Translated by Lin, Yiren; originally in After Nature's Revolt: Eco-justice and Theology, Dieter T. Hessel, ed.
Keywords: nature; landscapes; wildlands; environmental values; endangered species; Judaism; faith; Christianity; land ethic